Development of the Purification Process of Gallium-68 Eluted from Germanium-68/Gallium-68 Generator - Sriprapa, Tossaporn; Doungta, Thanete; Sritongkul, Napamon; Tantawiroon, Malulee (Siriraj Medical Journal, 2024)
Objective: 68Ga has a half-life of 68 minutes, with 89% of its decay is through positron emission. It is available from generator systems and possesses suitable property for labeling radioligands. These aspects make 68Ga a promising tracer for positron emission tomography (PET) imaging. This study aims to develop the purification process of the 68Ga eluates from 68Ge/68Ga generator after its recommended shelf-life and ensuring the quality through the radiolabeling process. Materials and Methods: In this study, we explored the development of a purification method for 68Ga eluted from a 68Ge/68Ga generator before radiolabeling was investigated. Cation and anion exchange chromatography techniques were combined to remove trace amounts of competing metal ion impurities. Post-purification, the eluate’s metal contents were analyzed using inductively coupled plasma atomic emission spectroscopy (ICP-AES). Breakthrough of 68Ge was measured using a multi-channel analyzer (MCA) spectrometer with high-purity germanium (HPGe) radiation detectors. Additionally, the radiochemical purity of 68Ga-NOTA-RGD was analyzed by high-performance liquid chromatography (HPLC). Results: Metal impurities including Fe(II), Zn(II) and Al(III) were reduced by 61%, 38% and 44% respectively. The 68Ge breakthrough was approximately ~10–3%. The labeling efficiency with NOTA-RGD, a tracer for angiogenesis imaging, resulted in an average yield of 68Ga-NOTA-RGD (not corrected for decay) of around 50%, with a radiochemical purity by HPLC of approximately 98%–99%. Conclusion: Cation exchange in combination with anion exchange chromatography was thus proven to be an efficient method for purification of the 68Ga eluate from a 68Ge/68Ga generator prior to labeling the 68Ga PET radiotracer.